Motivos externos e internos para la valoración financiera de los intangibles: Antecedentes y consecuentes - J. D. García Merino; G. Arregui Ayastuy; Arturo Rodríguez Castellanos; B. Vallejo Alonso (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2010)
This paper aims to analyse the Basque Country companies' view about the financial valuation of intangibles relevance and its influence on business performance. To achieve this objective, a field study has been done with 440 telephone calls to Basque Country companies' financial managers. Then, their responses and theirs firm's performance are analysed. The results show that the companies that are interested in the financial valuation of the intangibles, specially for internal motivation, perform better, however, this improvement is not statistically significant. Otherwise, the companies that are more interested in the valuation of their intangibles for external reasons need to provide information to stakeholders about their ability to generate income.
Keywords: M10; O16; G30; 330; intangibles; financial valuation of intangibles; managers' opinion; business performance